Optimizing Charter Scheme Selection for Coal Transport Vessels Through Capital Budgeting Indicators - Sandora, Rina; Hidayatullah, Muhammad Syarif (UNIPA PRESS, 2026)
Coal distribution via maritime transport is essential to meeting Indonesia’s national energy demands, creating business opportunities for bulk carrier operators and prompting a financial feasibility study on four investment schemes at a Surabaya-based shipping company: MV. Alpha (owned vessel) and MV. Beta (chartered vessel), each under Voyage Charter and Time Charter contracts. The assessment employs capital budgeting methods—Payback Period (PP), Net Present Value (NPV), and Benefit-Cost Ratio (BCR). Results show that all schemes are financially feasible. MV. Alpha–Voyage Charter records a PP of 4.6 months, NPV of Rp 41.1 billion, and BCR of 1.15, while Time Charter results in PP 7.4 months, NPV Rp 16.5 billion, and BCR 1.11. MV. Beta–Voyage Charter has a PP of 12.1 months, NPV Rp 15.3 billion, and BCR 1.03; whereas Time Charter achieves PP 5.3 months, NPV Rp 44.4 billion, and BCR 1.09. Incremental analysis reveals that MV. Alpha–Voyage Charter yields an incremental benefit of Rp 147.8 billion over Time Charter with an additional cost of Rp 123.2 billion, resulting in an incremental BCR of 1.20. For MV. Beta, Voyage Charter incurs Rp 29 billion in extra costs without added benefits, producing an incremental BCR of 0, making Time Charter the more efficient option.